2006
DOI: 10.1007/s10038-006-0087-0
|View full text |Cite
|
Sign up to set email alerts
|

Human organic cation transporter (OCT1 and OCT2) gene polymorphisms and therapeutic effects of metformin

Abstract: Organic cation transporters (OCTs) are responsible for the hepatic and renal transport of metformin. In this study we analyzed variants of OCT1 and OCT2 genes in 33 patients (24 responders and nine non-responders) based on the hypothesis that polymorphisms in both genes contribute to large interpatient variability in the clinical efficacy of metformin. The sequences of the 5¢-flanking and coding regions of the two genes of interest were screened by singlestrand conformation polymorphism (SSCP) analysis. To com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
152
3
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(164 citation statements)
references
References 18 publications
7
152
3
2
Order By: Relevance
“…18 Recently, it has been demonstrated that SNPs of the hepatic OCT1 gene in Caucasians and renal OCT2 gene in Koreans are responsible for the interindividual differences in the therapeutic efficacy and pharmacokinetics of metformin. [15][16][17] On the other hand, Shikata et al 25 reported that OCT1 and OCT2 polymorphisms contribute little to the clinical efficacy of metformin in Japanese. Previously, we demonstrated that metformin is a good substrate not only for OCT2 but also for MATE1 and MATE2-K. 19,26 Therefore, the SNPs of MATE1 and MATE2-K genes identified in this study may be involved in the interindividual difference in the renal clearance of metformin in Japanese.…”
Section: Discussionmentioning
confidence: 99%
“…18 Recently, it has been demonstrated that SNPs of the hepatic OCT1 gene in Caucasians and renal OCT2 gene in Koreans are responsible for the interindividual differences in the therapeutic efficacy and pharmacokinetics of metformin. [15][16][17] On the other hand, Shikata et al 25 reported that OCT1 and OCT2 polymorphisms contribute little to the clinical efficacy of metformin in Japanese. Previously, we demonstrated that metformin is a good substrate not only for OCT2 but also for MATE1 and MATE2-K. 19,26 Therefore, the SNPs of MATE1 and MATE2-K genes identified in this study may be involved in the interindividual difference in the renal clearance of metformin in Japanese.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32] Some of these variants were recently associated with a significantly decreased glucose-lowering response to metformin and altered metformin pharmacokinetics in healthy volunteers. 29,33 However, in another study, the prevalence of OCT1 variants did not differ between responders and nonresponders to metformin, 34 which may be due to different ethnic study populations or to a small number of subjects in the latter study. However, factors other than genetics may contribute to pharmacokinetic variability.…”
mentioning
confidence: 83%
“…In addition to drugdrug interaction studies, which have provided mechanistic information on the transporters involved in metformin renal elimination, human genetic studies have contributed immensely to our understanding of transporters involved in metformin renal elimination. In particular, in candidate gene studies in healthy volunteers, SLC22A2 and SLC47A1/SLC47A2 polymorphisms have been associated with changes in the pharmacokinetics and/or pharmacodynamics of metformin [54][55][56] .…”
Section: Transporters Involved In Metformin Renal Eliminationmentioning
confidence: 99%